Emerging Role of Neuronal Exosomes in the Central Nervous System - Chivet, Mathilde; Hemming, Fiona; Pernet-Gallay, karin; Fraboulet, Sandrine; Sadoul, Rémy (Frontiers in Physiology, 2012)
Abstract Exosomes are small extracellular vesicles, which stem from endosomes fusing with the plasma membrane, and can be recaptured by receiving cells. They contain lipids, proteins and RNAs able to modify the physiology of receiving cells. Functioning of the brain relies on intercellular communication between neural cells. These communications can modulate the strength of responses at sparse groups of specific synapses, to modulate circuits underlying associations and memory. Expression of new genes must then follow to stabilize the long-term modifications of the synaptic response. Local changes of the physiology of synapses from one neuron driven by another, have so far been explained by classical signal transduction to modulate transcription, translation and post-translational modifications. In vitro evidence now demonstrate that exosomes are released by neurons in a way depending on synaptic activity; these exosomes can be retaken by other neurons suggesting a novel way for interneuronal communication. The efficacy of inter-neuronal transfer of biochemical information allowed by exosomes would be far superior to that of direct cell to-cell contacts or secreted soluble factors. Indeed, lipids, proteins and RNAs contained in exosomes secreted by emitting neurons could directly modify signal transduction and protein expression in receiving cells. Exosomes could thus represent an ideal mechanism for inter-neuronal transfer of information allowing anterograde and retrograde signalling across synapses necessary for plasticity. They might also allow pathological proteins to spread across the nervous system.